2014
DOI: 10.1098/rsbl.2014.0892
|View full text |Cite
|
Sign up to set email alerts
|

When maths trumps logic: probabilistic judgements in chimpanzees

Abstract: When searching for hidden food, do chimpanzees take into account both the number of hidden items and the number of potential hiding locations? We presented chimpanzees with two trays, each of them containing a different food/cup ratio and therefore a different likelihood of finding a baited cup among empty alternatives. Subjects' performance was directly influenced by the relative difference ( probability ratio (PR)) between the two given probabilities. Interestingly, however, they did not appreciate the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 17 publications
(16 reference statements)
6
26
0
Order By: Relevance
“…The monkeys learned to choose those arrays with the greater ratio of positive to negative stimuli and were able to generalize to novel ratios. Similarly, as in the previously mentioned study with chimpanzees (Hanus & Call, ), the performance was directly influenced by the magnitude of difference between the two ratios to be discriminated. Interestingly, just as human infants (McCrink & Wynn, ), the two macaques tested were able to discriminate a ROR of 2, which is much lower than those used in our experiments.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The monkeys learned to choose those arrays with the greater ratio of positive to negative stimuli and were able to generalize to novel ratios. Similarly, as in the previously mentioned study with chimpanzees (Hanus & Call, ), the performance was directly influenced by the magnitude of difference between the two ratios to be discriminated. Interestingly, just as human infants (McCrink & Wynn, ), the two macaques tested were able to discriminate a ROR of 2, which is much lower than those used in our experiments.…”
Section: Discussionsupporting
confidence: 58%
“…Recent research suggests that indeed the magnitude of difference between two proportions is crucial for non‐human primates to discriminate probabilities. Hanus & Call () presented chimpanzees with two trays, each of them with a different ratio of hidden food items to potential hiding locations and therefore a different likelihood of finding food. This study revealed that subjects’ performance was influenced by the relative difference between the two probabilities as soon as a certain threshold thereof was reached.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the present findings may reflect true competence limitations and show that macaques are incapable of using intuitive statistics (although they might still be able to engage in statistical reasoning using other formats of information, such as frequencies of sequential events for example, an ability highlighted in chimpanzees 24 ). While the present findings cannot rule out their lack of competence, one piece of evidence seems to speak against it: Maja (and Sally to a lesser extent) performed well in most conditions.…”
Section: Discussionmentioning
confidence: 78%
“…Recently, similar reasoning abilities were highlighted in nonhuman primates: four species of apes 22 , and one species of capuchins 23 were able to use populations of food items to form expectations about sampling events, based on a paradigm originally developed for children 15 . Another study showed that chimpanzees used proportional information to infer which of two trays containing different food/cup ratios was more likely to yield a cup containing food 24 . These studies are interesting in two aspects.…”
Section: Introductionmentioning
confidence: 99%
“…One recent study did find some such evidence for an involvement of the analogue magnitude system in decision making under uncertainty in nonhuman great apes: Hanus and Call (2014) gave chimpanzees the choice between two trays on which food items were hidden under cups. The trays differed with respect to the ratio of food items to cups and thus in chances of finding food.…”
Section: Mccrink and Wynnmentioning
confidence: 99%